2003
DOI: 10.1007/s00247-002-0838-9
|View full text |Cite
|
Sign up to set email alerts
|

Classification of venous malformations in children and implications for sclerotherapy

Abstract: Our initial results indicate that sclerotherapeutic intervention in patients with type-III and type-IV VMs must be carefully considered, while it can be safely performed in low-risk patients with type-I and type-II lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
114
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(139 citation statements)
references
References 28 publications
10
114
1
5
Order By: Relevance
“…In fact, a recent study suggested the classification of VMs into 4 groups on the basis of presence and morphology of venous drainage, showing that sclerotherapy alone was most useful for those lesions with no peripheral drainage or drainage into normal veins. 67 The specific management of these lesions depends on the location of the lesion. Thus it is useful to divide VMs into two broad categories when considering their management: (1) head and neck VMs and (2) trunk and limb VMs.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…In fact, a recent study suggested the classification of VMs into 4 groups on the basis of presence and morphology of venous drainage, showing that sclerotherapy alone was most useful for those lesions with no peripheral drainage or drainage into normal veins. 67 The specific management of these lesions depends on the location of the lesion. Thus it is useful to divide VMs into two broad categories when considering their management: (1) head and neck VMs and (2) trunk and limb VMs.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Elle doit être interrompue 12 heures avant le geste [11]. De plus, une sclérothérapie peut être envisagée en cas de gêne esthétique ou fonctionnelle, en particulier, dans les cas d'atteinte articulaire et en cas de douleurs chroniques [12]. Elle peut être complétée par une exérèse chirurgicale surtout dans les localisations musculaires [13].…”
Section: Discussionunclassified
“…Subsequently, the lesion shrinks down in size due to permanent obliteration of vessels by organized thrombi, intimal necrosis and adventitial fibrosis. The method seems to be especially effective if the draining vessels of the malformation are of normal calibre and do not show dilatation or ectatic changes [12]. The favoured sclerosing agent used in this setting is absolute ethanol, for which good results with limited complications rates (e.g.…”
Section: Comparison Of Pdt To Conventional Therapies For Venous Malfomentioning
confidence: 99%